Blue Natural Capital : Enhancing Business Outcomes and Sustainability of Coastal Tourism Markets - White, Elizabeth M. (International Finance Corporation, Washington, DC, 2021)
The Coronavirus (COVID-19) pandemic hit the tourism industry particularly hard, affecting livelihoods and exacerbating some pressures on the natural capital resource base. Supporting the tourism sector recovery is an opportunity to build back better, ensuring that business investments lead to a sustainable and resilient shared-growth pathway that is good for tourism and the natural capital on which it depends. Further sustainable management of the Blue economy could more than double its economic contribution to global relationship with economic sectors across coastal landscapes and markets. The experience of the State of Palawan in the Philippines is explored in this note. It serves as a useful model for weighing the opportunities and challenges typical of coastal tourism areas and exploring natural dependencies therein.